2018
DOI: 10.1002/jcb.27858
|View full text |Cite
|
Sign up to set email alerts
|

Does proliferation capacity of lymphocytes depend on human blood types?

Abstract: In vitro human lymphocyte culture methodology is well established yet certain confounding factors such as age, medical history as well as individual’s blood type may potentially modulate in vitro proliferation response. These factors have to be carefully evaluated to release reliable test report in routine cytogenetic evaluation for various genetic conditions, radiation biodosimetry, etc. With this objective, the current study was focused on analyzing the proliferation response of lymphocytes drawn from 90 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
3
2
0
Order By: Relevance
“…Generally, most of the relevant studies have presented frequencies of acentric fragments or rings for one or a few donors (2-5) as a distribution for the dose-response curve construction [10,15]. The baseline mean value of NDI for the control group (1.71 ± 0.11) was in agreement with previously published data [10,16]. For the exposed group, the averaged mean was higher (3.04 ± 0.86), indicating that viable cells divided faster than in the control group and completed more than one nuclear division during the cytokinesis-block phase.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Generally, most of the relevant studies have presented frequencies of acentric fragments or rings for one or a few donors (2-5) as a distribution for the dose-response curve construction [10,15]. The baseline mean value of NDI for the control group (1.71 ± 0.11) was in agreement with previously published data [10,16]. For the exposed group, the averaged mean was higher (3.04 ± 0.86), indicating that viable cells divided faster than in the control group and completed more than one nuclear division during the cytokinesis-block phase.…”
Section: Discussionsupporting
confidence: 87%
“…The observed results could have arisen due to confounding factors affecting MNi frequency levels in humans, such as smoking, diet or environmental exposures [4,13,16,17]. Although we did not stratify subgroups according to the daily consumption of cigarettes, as has been done by others [23], our observations are supported by these findings, suggesting that smoking can affect the level of genetic damage induced in humans by ionizing radiation.…”
Section: Discussionsupporting
confidence: 64%
“…The manual MI values of all donors in this study are also comparable with a previous study by Viswanathan et al (2019) that found the percentage of MI in different blood types were varied widely. The rate of MI in variety A ranged from 4.39 to 18.6%, with mean ± SD values of 11.0 ± 4.3%.…”
Section: Resultssupporting
confidence: 89%
“…Studies of T cell dynamics, at least for humans, are most often based on samples from the blood. Directly ex vivo , most peripheral blood T lymphocytes are in G0 \ G1 [27, 28]. Nevertheless high levels of deuterium are typically detected in peripheral blood lymphocytes following a labelling period.…”
Section: Resultsmentioning
confidence: 99%